2022
DOI: 10.3390/su14095040
|View full text |Cite
|
Sign up to set email alerts
|

Studying Waste Separation Behaviors and Environmental Impacts toward Sustainable Solid Waste Management: A Case Study of Bang Chalong Housing, Samut Prakan, Thailand

Abstract: This study aims to develop more inclusive and sustainable waste management practices to be implemented in Bang Chalong Housing, a model community with unsatisfactory waste separation and recycling rate. The extended theory of planned behavior was employed to investigate the effect of attitude, subjective norm, perceived behavioral control, knowledge, and situational factors on household waste separation intention and behavior, using structural equation modeling as a tool. Based on the questionnaire responses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 99 publications
0
2
0
1
Order By: Relevance
“…Hasil penelitian terhadap karyawan lapangan PT. X yang berjenis kelamin laki-laki menunjukkan bahwa terdapat korelasi positif antara persepsi kontrol perilaku dan niat Faktor demografi seperti usia dan pendidikan menunjukkan hubungan yang sangat lemah dengan perilaku memilah sampah, tetapi usia tidak dapat dijadikan parameter signifikan perilaku memilah sampah (Pongpunpurt et al, 2022). Pendidikan memiliki nilai hubungan searah dengan perilaku memilah sampah, tetapi lebih lemah dibandingkan dengan usia.…”
Section: Diskusiunclassified
“…Hasil penelitian terhadap karyawan lapangan PT. X yang berjenis kelamin laki-laki menunjukkan bahwa terdapat korelasi positif antara persepsi kontrol perilaku dan niat Faktor demografi seperti usia dan pendidikan menunjukkan hubungan yang sangat lemah dengan perilaku memilah sampah, tetapi usia tidak dapat dijadikan parameter signifikan perilaku memilah sampah (Pongpunpurt et al, 2022). Pendidikan memiliki nilai hubungan searah dengan perilaku memilah sampah, tetapi lebih lemah dibandingkan dengan usia.…”
Section: Diskusiunclassified
“…investigated that environmental regulation plays a significant role in behavioral intention for household waste classification. Pongpunpurt et al in 2022 [8] demonstrated that waste classification intention was predicted by four factors, name, knowledge, subjective norms, and current behavior. Bardus and Massoud [9] concluded that waste separation intention was predicted by controlling perceived behavior, perceived norms, and present behavior.…”
Section: Introductionmentioning
confidence: 99%
“…By the end of 2020, about 46 million tons of waste has accumulated in landfills across the country [20]. Some important problems related with the MSW management activities arise not only in Kazakhstan [21], but also in many countries around the world such as the USA [22], Saudi Arabia [23], Dominican Republic [24] and Thailand [25]. Some of these problems are: (i) lack of licensed landfills, (ii) increasing number of unauthorized landfills, (iii) increasing production of solid household waste, (iv) lack of waste recycling facilities, (v) lack of funding and (vi) poor conditions for business and entrepreneurship development.…”
Section: Introductionmentioning
confidence: 99%